1977
DOI: 10.1210/jcem-45-6-1313
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide Increases Plasma Aldostergne Concentration in Man

Abstract: Plasma Aldosterone (PA) response to metoclopramide (10 mg i.v.) was studied in 11 normal, 2 hypophysectomized subjects and in one patient with bilateral adrenal hyperplasia. All the subjects were kept on a normal sodium and potassium intake. Four normal subjects were pretreated with 1 mg of dexamethasone in order to inhibit endogenous ACTH. In all subjects metoclopramide elicited a prompt rise of PA comparable to that obtained with angiotensions or ACTH. No significant change of blood pressure, serum electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(53 citation statements)
references
References 0 publications
5
46
1
1
Order By: Relevance
“…Norbiato et al (30) reported that an intravenous bolus dose (10 mg) of metoclopramide increased plasma aldosterone concentration in dexamethasone-suppressed normal subjects, patients with primary aldosteronism due to idiopathic adrenal hyperplasia and hypophysectomized subjects, without altering plasma ll-OHCS or potassium concentrations or plasma renin activity. However, no placebo control study was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Norbiato et al (30) reported that an intravenous bolus dose (10 mg) of metoclopramide increased plasma aldosterone concentration in dexamethasone-suppressed normal subjects, patients with primary aldosteronism due to idiopathic adrenal hyperplasia and hypophysectomized subjects, without altering plasma ll-OHCS or potassium concentrations or plasma renin activity. However, no placebo control study was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide used gastroprokinetic and antiemetic agent metoclopramide is known to exert stimulatory effects on prolactin and aldosterone secretions in human subjects (Norbiato et al 1977, Harrington et al 1983). …”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators, like us, have only evaluated the significance of changes in cortisol concentration between the basal and the response level after administration of metoclopramide and have found no significant difference (Brown et al, r-nn L 1981;Norbiato et al, 1977). However, when the normal diurnal variation in cortisol was taken into account, a rise in cortisol at 40 min was observed after administration of metoclopramide (Nishida et al, 1983a).…”
Section: Discussionmentioning
confidence: 72%
“…A further well known modulator of aldosterone is dopamine (Carey et al, 1979). Metoclopramide, a dopaminergic DA2-receptor antagonist, is believed to stimulate aldosterone release by causing withdrawal of dopaminergic inhibition of aldosterone release (Edwards et al, 1980;Norbiato et al, 1977;Noth et al, 1980). We have therefore now conducted a study to investigate the effect of ANF on the aldosterone response to metoclopramide in man.…”
Section: Introductionmentioning
confidence: 99%